Analisis Keberhasilan Kampanye Iklan dalam Proses Pengambilan Keputusan Memilih Perguruan Tinggi - Dion Dewa Barata (Ultima Management : Jurnal Ilmu Manajemen, 2010)
Advertising is more then just informing audience. In conducting its marketing strategy, higher education institution use advertising as a tool to communicate information and shape perceptions. This study tried to analyze the impact of advertising campaigns against the formation of brand awareness and brand perception of the higher education institution which then affect the prospective student’s decision to choose the right higher education institution for them. Using a prospective student respondents, the study found that brand awareness does not have a significant influence on their decision, if not supported by brand perception of higher education institution. Keywords: Marketing Strategy, brand, education, university, awareness, perception, advertising